Pengaruh Kualitas Pelayanan dan Harga terhadap Kepuasan Pelanggan di Laulau Cafe Lebak Bulus - Iis Noviyanti; Lia Asmalah; Riri Oktarini (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
In today’s competitive cafe industry, customer satisfaction has become a crucial determinant of business sustainability and growth. LauLau Cafe Lebak Bulus faces the challenge of maintaining customer loyalty while delivering high-quality service and reasonable pricing. This study aims to examine the effect of service quality and price, both partially and simultaneously, on customer satisfaction at LauLau Cafe Lebak Bulus. A quantitative research approach with a survey method was employed. The population consisted of 7,655 cafe consumers, and a sample of 99 respondents was determined using Slovin’s formula and selected through simple random sampling. Data were collected through a structured questionnaire distributed directly and via WhatsApp, designed using Google Forms with closed-ended Likert scale questions. Data analysis was conducted using SPSS 26, including descriptive statistics, validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The results indicate that both service quality and price have a positive and significant effect on customer satisfaction, individually and simultaneously. This finding highlights that customer satisfaction is influenced not only by the quality of service but also by the perceived fairness of pricing. Therefore, cafe management should continuously enhance service quality while maintaining competitive pricing strategies to foster customer loyalty, improve retention, and strengthen market position sustainably.